Quantifying differences in head kinematics associated with tackle form in youth football - Holcomb, T. D.; Marks, M. E.; Bullock, G. S.; Filben, T. M.; Lazzara, B.; Moore, J. B.; Miles, C. M.; Stitzel, J. D.; Urban, J. E. (Journal of Sports Sciences, 2025)
American football has a high rate of concussion and subconcussive head impacts resulting from tackling collisions. A tackle must be properly executed to maximize safety for involved athletes. The study objective was to develop a grading rubric and evaluate the relationship between tackle form and head kinematics in youth football. A grading rubric was co-developed with stakeholders and informed by standards for tackling. Head kinematic data were collected from 14 youth athletes via instrumented mouthpiece. Mixed-effects models, linear regression, and least absolute shrinkage and selection operator (LASSO) analysis was used to examine the data. A total of 149 head acceleration events (HAEs) that occurred across 125 tackles were collected. The median [95th percentile] peak linear acceleration (PLA), rotational acceleration (PRA), and rotational velocity (PRV) measured from tackling HAEs were 12.9 g [31.2 g], 927 rad/s2 [2582 rad/s2], and 9.8 rad/s [18.9 rad/s] respectively. Greater tackle form score was associated with lower biomechanics on average. Tackles where tacklers lowered their head or allowed their head to cross the body of the ball carrier led to higher magnitude HAEs. The results of this study help inform targets for individual-level interventions targeting tackle form as a method of reducing head impact exposure.